Synthesis and Characterization of Cassava Shell Based Biodegradable Plastic with Kitosan Addition - Supriyono Supriyono; Hamdan Hadi Kusuma; Mulyatun Mulyatun; Biaunik Niski Kumila (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2017)
Wasted-plastic which is a hardly-decomposed material was one of the major problems of trash-recycling management in Indonesia. Replacing a common plastic with biodegradable plastic was one of the solution to reduce the amount of undecomposed-materials in the enviroment. Therefore, the aim of this resarch is to study how to synthesis cassava shell based biodegradable plastic and to analyse the effect of kitosan addition on cassava shell based biodegradable plastic properties. There are three basic characterization processes performed to analyse the sample properties, i.e mechanical test, FTIR and biodegradability test. Kitosan enhanced the mechanical and biodegradability properties of samples. The elongation-percentage decreased down to 8,57% along with the increasing the amount of kitosan concentration. FTIR data indicated the presence of O-H, N-H, C-H, C=C, NO2 and C-O organic functional group on biodegradable plastic samples. Kitosan reduce the decomposition process of samples due to its hydrophilicity. Sample with highest concentration of kitosan decomposed at the longest time up to 14 days. . ©2017 JNSMR UIN Walisongo. All rights reserved.